Shariah Governance and Halal Compliance of Cultured Meat: A Maqasidi Analysis of in Vitro Meat Production - Luqman Abu Tayyab (Indonesian Journal for Islamic Studies, 2026)
Background: Cultured meat, produced through cellular bioprocessing rather than conventional slaughter, raises substantial and largely unresolved questions for Islamic dietary law and halal governance, and no study to date has integrated the complete Maqasid al-Shariah framework with a comparative assessment of international halal regulatory infrastructure.Objectives: This study evaluates the Shariah governance dimensions and halal compliance requirements of cultured meat through the five essential interests (al-kulliyyat al-khams) of Maqasid al-Shariah and identifies substantive gaps in existing halal certification infrastructure.Methods: A qualitative doctrinal (usul al-fiqh) methodology was employed, drawing on the Quran, Sunnah, and classical fiqh manuals of the four Sunni madhabs, contemporary fatawa, and international halal standards (OIC/SMIIC, JAKIM, GSO, MUIS), supplemented by a systematic mapping of peer-reviewed literature (2018–2026) on cultured meat and Islamic bioethics.Results: Cultured meat occupies a novel legal space (fiqh al-mustajaddat), generating three scholarly positions conditional permissibility, prohibition, and tawaqquf. Three governance gaps were identified across existing halal standards: absent biopsy protocol specifications, no framework for evaluating growth media (notably Foetal Bovine Serum), and structural inapplicability of conventional chain-of-custody models to continuous bioprocess production. The May 2025 resolution of the International Islamic Fiqh Academy conditionally permitting cultivated meat corroborates the governance-centred trajectory this study proposes.Conclusion: Cultured meat requires purpose-built Shariah governance combining scholarly ijtihad, institutional oversight, and a 'Shariah-by-design' approach. The study contributes a Maqasidi cost-benefit framework and a four-tier governance architecture to Islamic regulatory discourse.